Applicability of immersive virtual reality for training with the myoelectric prosthesis in upper extremity amputated patients: "A clinical case report" - Jordi Calvo Sanz; Lluis Guirao Cano; Beatriz Samitier Pastor; M Angeles Díaz Vela; Vanesa Rodríguez Salés; Pol Monné Cuevas (Journal of Novel Physiotherapy and Physical Rehabilitation - Peertechz Publications, 2022)
The integration of Virtual Reality (VR) in the rehabilitation process of the upper extremity amputee patient reinforces motor learning, facilitates the incorporation of the prosthesis in the body scheme, and normalizes global gesturing.